2022
DOI: 10.3389/fcvm.2022.885293
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits NF-κB/CREB/Runx2 Signaling and Alleviates Aortic Valve Calcification

Abstract: Calcific aortic valve disease (CAVD) is linked to high mortality. Melatonin inhibits nuclear factor-kappa B (NF-κB)/cyclic AMP response element-binding protein (CREB), contributing to CAVD progression. This study determined the role of melatonin/MT1/MT2 signaling in valvular interstitial cell (VIC) calcification. Western blotting and Alizarin red staining were used to analyze NF-κB/CREB/runt-related transcription factor 2 (Runx2) signaling in porcine VICs treated with an osteogenic (OST) medium without (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Recently, Candellier et al demonstrated that indoxyl-sulfate promotes osteogenic differentiation of hVIC via an activation of the AhR-NF-κB pathway [ 29 ]. Our preclinical model could be used to evaluate the impact of therapies inhibiting NF-κB signaling, including melatonin [ 31 ], aspirin [ 32 ], or metformin [ 33 ], on radiation-induced aortic remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Candellier et al demonstrated that indoxyl-sulfate promotes osteogenic differentiation of hVIC via an activation of the AhR-NF-κB pathway [ 29 ]. Our preclinical model could be used to evaluate the impact of therapies inhibiting NF-κB signaling, including melatonin [ 31 ], aspirin [ 32 ], or metformin [ 33 ], on radiation-induced aortic remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…121 As well as blocking NF-κB activation signaling, melatonin inhibits the activity of IKK receptors. 122 Furthermore, melatonin regulates cytokine signaling pathways, including the Janus kinase/signal transducer and activator of transcription (JAK/STAT) family pathway, impacting immune cell function and the development of inflammatory responses. 123 These signaling pathways play an important role in the inflammatory response, and melatonin inhibits the onset and progression of the inflammatory response by regulating their activity.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“… 121 As well as blocking NF-κB activation signaling, melatonin inhibits the activity of IKK receptors. 122 Furthermore, melatonin regulates cytokine signaling pathways, including the Janus kinase/signal transducer and activator of transcription (JAK/STAT) family pathway, impacting immune cell function and the development of inflammatory responses. 123 …”
Section: Melatonin Exerts Antioxidant Anti-inflammatory Cytoprotectiv...mentioning
confidence: 99%
“…Hence, one of the causes of ferroptosis is an iron overload that is involved in CAVS by enhancing calcium deposition and calcification in endothelial cells (HUVEC) [ 90 ]. It is identified that the endothelial cells play crucial impacts in the calcification process through the EndMT [ 91 ]. Multiple pathways are involved in this process including the signaling pathways involved in hypoxia and inflammation, such as the transforming growth factor beta (TGF-β) signaling pathway [ 92 ], and the Wnt signaling pathway [ 93 , 94 ].…”
Section: The Complex Interplay Of Hypoxia Signaling Mitochondrial Dys...mentioning
confidence: 99%